Development of Volta Drive Connect Media to Strengthen Energy Literacy of Elementary School Students - Firnanda Millatin Afina; Ahmad Khoiri; Vava Imam Agus Faisal (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Science learning in elementary school often faces obstacles in conveying abstract concepts such as energy transformation, so it requires concrete learning media. This research aims to develop Volta Drive Connect, a project-based science teaching kit in the form of a solar-powered toy car, and to test its feasibility, practicality, and effectiveness in improving students' energy literacy. Using the Research and Development (R&D) method with the ADDIE model, this research was conducted with grade IV students at SD Nasional Kakuka and SD Negeri Simbarejo. The results of expert validation show that the design of the materials and media is highly feasible. In the effectiveness test, Volta Drive Connect proved to be significant in improving students' energy literacy. This was demonstrated by the paired-samples t-test (p<0.05), indicating an increase in the average score from 66.8 to 78.3. The use of this media not only motivates students and increases environmental awareness but is also aligned with the achievement of the Sustainable Development Goals (SDGs). In practice, this media provides an alternative innovative solution for teachers in facilitating student-centered basic science learning. In addition, the implementation of Volta Drive Connect encourages students to actively participate in learning through hands-on experimentation and collaborative activities. Students are involved in assembling and testing solar-powered toy cars, allowing them to understand the concept of energy transformation through real-world experiences. It also supports the development of science process skills, such as observation, problem-solving, and teamwork, which are important competencies in basic science education. Therefore, Volta Drive Connect not only contributes to improving students' conceptual understanding of energy but also to fostering positive attitudes towards renewable energy and sustainable environmental practices.